Promising Response with PI3K Inhibitor for a Patient with Heavily Pretreated PIK3CA Mutation Head-and-Neck Cancer - Ming-Jing Lee; Hsiang-Fong Kao (Journal of Cancer Research and Practice)
The treatment options for patients with head-and-neck squamous cell carcinoma (HNSCC) are limited when the disease progresses after taking platinum, a PD-1 inhibitor, and cetuximab. To develop new agents for managing such pretreated malignancies, therapies targeting carcinogenic pathways could be possible in HNSCC patients. Several pathways have been identified in HNSCC, including the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway. The PI3K/AKT/mTOR pathway is frequently dysregulated in various cancers due to activating mutations or amplification of PIK3CA. The inhibition of this pathway has been proven to improve clinical outcomes in some malignancies with PIK3CA mutations. We report a heavily pretreated HNSCC patient with a good treatment response to alpelisib, a PI3K inhibitor. Furthermore, we discuss the possible limitations of alpelisib monotherapy and possible solutions to overcome these limitations.